2018
DOI: 10.1016/j.hermed.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Antiprotozoal properties of Indonesian medicinal plant extracts

Abstract: Tithonia diversifolia, Cyclea barbata, Tinospora crispa, Arcangelisia flava, Pycnarrhena cauliflora are plants used in Indonesia for the traditional treatment of malaria. In the search for new antiparasitic drugs, the parts traditionally used of these 5 plants were extracted with various solvents and evaluated in vitro against Plasmodium falciparum but also against Babesia divergens and Leishmania infantum. Seven crude plant extracts out of 25 tested displayed high antimalarial activities with IC50 < 5 µg/ml a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
1
6
0
2
Order By: Relevance
“…In the South Kerala region of India, locals use the plant as an antidiabetic (Thomas et al 2016 ). The use of T. crispa as an antimalarial agent is widespread in Malaysia, the Philippines, Indonesia, Vietnam, Southern Laos and the Republic of Guinea (Forman 1981 ; Ahmad and Ismail 2003 ; Bertani et al 2005 ; Elkington et al 2014 ; Ramadani et al 2018 ; Dapar 2020 ; Dapar et al 2020 ). Indonesians also employ the plant for hyperglycemia, inflammation, fever and rheumatism.…”
Section: Ethnomedicinal Usesmentioning
confidence: 99%
“…In the South Kerala region of India, locals use the plant as an antidiabetic (Thomas et al 2016 ). The use of T. crispa as an antimalarial agent is widespread in Malaysia, the Philippines, Indonesia, Vietnam, Southern Laos and the Republic of Guinea (Forman 1981 ; Ahmad and Ismail 2003 ; Bertani et al 2005 ; Elkington et al 2014 ; Ramadani et al 2018 ; Dapar 2020 ; Dapar et al 2020 ). Indonesians also employ the plant for hyperglycemia, inflammation, fever and rheumatism.…”
Section: Ethnomedicinal Usesmentioning
confidence: 99%
“…Sampel bubuk C. barbata diekstraksi dengan maserasi dalam etanol 70% dan memiliki nilai IC50 > 50 μg/ml. Meskipun digunakan secara tradisional untuk mengobati malaria, namun ekstrak C. barbata tidak menunjukkan aktivitas antiplasmodial dari uji ini (Ramadani et al, 2018) Aktivitas antiplasmodial dari ekstrak alkaloid bisbenzylisoquinoline C. barbata diuji secara in vitro dengan metode penggabungan radioisotop. Alkaloid…”
Section: Antiplasmodialunclassified
“…16 . Ramadani et al 2017, demonstrated that dichloromethane and methanol fractions P. cauliflora (Menispermaceae) radix, have high activity against L. infantum, with IC50 values around 3 μg/ml; their high selectivity index, especially on VERO cells, hypothesises a specific parasiticidal action (26). Ahmed et al 2017, evaluated the antileishmanial capability of different extracts of Quercus dilatata Lindl, the evaluation of test extracts was carried out by employing MTT colorimetric assay and found the Ethyl acetate + Acetone and Acetone extracts exhibited remarkable and comparable leishmanicidic potential with IC 50 12.91 ± 0.02 μg/ ml and 14.40 ± 0.01 respectively and it was found to be absent in the polar extracts.…”
Section: Leishmaniasismentioning
confidence: 99%
“…Smyrniotopoulos et al 2017, tested for in vitro antiprotozoal activity towards a small panel of parasites (Plasmodium falciparum, Trypanosoma brucei rhodesiense, T. cruzi, and Leishmania donovani) and cytotoxicity against mammalian primary cells the Irish brown alga Bifurcariabifurcata (Sargassaceae family).They observed highest activity was exerted against the malaria parasite P. falciparum (IC50 value 0.65 μg/mL) with low cytotoxicity (IC50 value 56.6 μg/mL) 19 . Ramadani et al 2017, found A. flava (Menispermaceae) highest antiplasmodial activity (IC50 values less than 3 μg/ml) and the weakest cytotoxicity (26). Vasquez-Ocmin et al 2018, report that the ethanolic extract from Costus curvibracteatus (Costaceae) leaves, Griasneuberthii (Lecythidaceae), Stachytarpheta cayennensis, and Alchornea triplinervia showed strong in vitro activity on P. falciparum (sensitive and resistant strain), suggesting that these activities could be attributed to the main arylpropanoid and iridoid constituents (verbas-coside, isoverbascoside and ipolamiide), of phenolic compounds in the plant leaves (9).…”
Section: Plasmodium (Malaria)mentioning
confidence: 99%
See 1 more Smart Citation